PERAN ONLINE ADVERTISING PADA PEMASARAN AXIS - Eka Santi, Devita (Universitas Teuku Umar, 2020)
Abstract:Â In this era of the growth of technology, the internet user is significantly increasing each year. During advertising activities, companies start using internet to advertise their products or services. Online advertising activities keep increasing dramatically. Advertising business do much more activities on internet to send message as marketing form to audiences. There are various online advertising using the internet nowadays. Online advertising is done to build awareness until purchase decision of the products or services which has been advertised to the audiences. In this research has been described various types of online advertising that has been done by Axis, such as search engine optimization, search engine marketing, social media advertising, and placement banner. Online advertising which has been done by Axis is to build awareness, consideration, purchase decision to the audiences who access the online advertising. Online advertising is done to reach the target audiences of Axis and instill Axis brand in the mind of the audiences (top of mind)Â Keywords: Advertising, Online Advertising, Build Awareness, Purchase Decision